2015
DOI: 10.1007/s11090-015-9640-y
|View full text |Cite
|
Sign up to set email alerts
|

Microplasma: A New Generation of Technology for Functional Nanomaterial Synthesis

Abstract: Plasma technology has been widely applied in the ozone production, material modification, gas/water cleaning, etc. Various nanomaterials were produced by thermal plasma technology. However, the high temperature process and low uniformity products limit their application for the high value added chemicals synthesis, for example the functional materials or the temperature sensitive materials. Microplasma has attracted significant attentions from various fields owing to its unique characteristics, like the highpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 188 publications
(270 reference statements)
0
68
0
Order By: Relevance
“…[20] Such surface functionalities favor good dispersion of catalyst nanoparticles on rGO carrier increasing the electrochemically active surface area. [30][31][32][33][34] Plasma jet method provides good controllability, cleanliness and selectivity. [4,[22][23][24] The most common preparation method of graphenesupported Pt nanostructures is based on the reduction of GO and Pt precursors (K 2 PtCl 4 or H 2 PtCl 6 ) via different chemical and physical approaches, such as chemical reduction, photochemical method, microwave assisted preparation, electroless deposition and thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Such surface functionalities favor good dispersion of catalyst nanoparticles on rGO carrier increasing the electrochemically active surface area. [30][31][32][33][34] Plasma jet method provides good controllability, cleanliness and selectivity. [4,[22][23][24] The most common preparation method of graphenesupported Pt nanostructures is based on the reduction of GO and Pt precursors (K 2 PtCl 4 or H 2 PtCl 6 ) via different chemical and physical approaches, such as chemical reduction, photochemical method, microwave assisted preparation, electroless deposition and thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] The use of plasma-liquid interaction, where charge transfer processes take place, is currently a rapidly developing alternative technique for preparation of catalyst nanoparticles. [30][31][32][33][34] Plasma jet method provides good controllability, cleanliness and selectivity. It can tune optical and electronic properties of graphene, besides it is cost and time-effective.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Preceding studies have shown that particle size, morphology, composition, and microstructure can be tuned through processing parameters. 15 Moreover, as reactions take place in the gas phase, hazardous wet chemistry is not involved, rendering it to be a promising protocol for nanomaterial fabrication, especially for bio-application purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric Pressure DC Microplasma is the simplistic, environmentally acceptable, fast, and cost effectual plasma-liquid interaction system. Microplasmas are non-Local Thermodynamic Equilibrium (non-LTE), high-pressure discharges that can be handled at room temperature, atmospheric pressure, low rate of gas flow, moderate current and voltage [35][36][37]. Some noteworthy characteristics of microplasma which make them appreciable for the growth of nanoparticles include high-pressure chemistry, facile reactor geometry, uninterrupted flow and self accumulation of nanostructures formed by microplasma methods, high radical densities [38][39][40] and most importantly the connection of microplasma with solutions [41,42].…”
Section: Introductionmentioning
confidence: 99%